Potential Role and Prognostic Value of Interleukin-15 for Mortality Among Elderly Patients with Sepsis - Zhao J; Zhang Y; Wang J; Wei B; Liu Y (Dove Medical Press, 2023)
Jingjing Zhao,1 Ye Zhang,2 Junyu Wang,2 Bing Wei,2 Yugeng Liu1,2 1Department of Infectious Disease and Clinical Microbiology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100043, People's Republic of China; 2Emergency Medicine Clinical Research Center, Beijing Chaoyang Hospital & Beijing Key Laboratory of Cardiopulmonary Cerebral Resuscitation, Clinical Center for Medicine in Acute Infection, Capital Medical University, Beijing, 100043, People's Republic of ChinaCorrespondence: Bing Wei; Yugeng Liu, Emergency Medicine Clinical Research Center, Beijing Chaoyang Hospital, Capital Medical University, 5 Jing-Yuan Road, Beijing, 100043, People's Republic of China, Email dr_weibing@126.com; 13466751067@126.comBackground: To investigate the potential role and prognostic value of interleukin-15 (IL-15) in predicting 28-day mortality in elderly patients with sepsis.Methods: According to the Sepsis-3.0 diagnostic criteria for sepsis, elderly patients with sepsis who were admitted to the emergency department of the Shi jingshan branch of Beijing Chaoyang Hospital between October 2021 and June 2022 were enrolled in this retrospective cohort study. After observation for 28 days, patients were divided into a survival group and a nonsurvival group. Samples for laboratory tests, baseline characteristic data, and SOFA and Acute Physiology and Chronic Health Evaluation (APACHE II) scores were collected or recorded within 24 h after admission to the emergency department. Quantitative detection of IL-15 was performed with a Luminex assay. Logistic regression analysis and receiver operating characteristic curve (ROC) analysis were conducted for comparison.Results: In total, 220 elderly patients with sepsis were enrolled, 69 of whom were in the survival group and 151 of whom were in the nonsurvival group at the 28-day interval. Systolic pressure, high-density lipoprotein (HDL), platelets (PLT) and albumin (ALB) were significantly higher in the survival group (P< 0.05), while IL-15, SOFA, and APACHE II were significantly higher in the nonsurvival group (P< 0.05). IL-15 was an independent risk factor associated with 28-day mortality (OR=1.842, 95% CI [1.323, 2.565]). The area under the receiver operating characteristic curve (AUROC) of IL-15 alone was 0.691 (95% CI [0.618, 0.764]), with a sensitivity of 46.67% and a specificity of 85.81%. The AUROC of the combined IL-15 and SOFA reached 0.880 (95% CI [0.672, 0.812]), for which the sensitivity and specificity were 80.95% and 85.08%, respectively.Conclusion: IL-15 possesses the prognostic value for predicting 28-day mortality in elderly patients with sepsis.Keywords: elderly patients, sepsis, interleukin-15, platelet, albumin, SOFA, APACHE II